Institutional Participation and Earnings Information Quality: Empirical Evidence from China - Cheng Min (European Scientific Journal, ESJ, 2018)
Recently many scholars are greatly concerned about the influence of institutional investors on companies’ earnings information quality. Institutional investors have strong and professional team. With big fund stake on listed companies, institutional investors are theoretically thought of playing active role in supervising companies to ensure their investment safety and return. Much evidence has showed that institutional investors are becoming active institutional participation from past passive shareholders. The characteristics of institutional show great advantages on exerting their effect on corporate governance. Correspondingly positive behavior of institutional investors will influence the degree of the accounting information quality. Based on this concept, institutional investors can discover in a timely and effective manner problems existing in the accounting information disclosure. As a result, this article examines whether institutional investors as active shareholders can participate in corporate governance in order to improve companies’ accounting information quality.